MEMBANGUN KESADARAN SOSIAL MAHASISWA STAI DARUL FALAH MELALUI PARTISIPASI DALAM KEGIATAN BAKTI SOSIAL DONOR DARAH - Ayu Puji Rahayu; Fikri Rizkia Muhammad; Mohammad Sabarudin; Murharyana Murharyana (LPPM STAI Darul Falah, 2023)
Community service activities (PkM) in the KKN program can be used as a vehicle for the application and development of knowledge outside the campus. Through the voluntary blood donor social service program, it is hoped will increase the social awareness of STAI Darul Falah students about public health problems. The activity with the theme